2021
DOI: 10.3390/polym13193425
|View full text |Cite
|
Sign up to set email alerts
|

Crazing Effect on the Bio-Based Conducting Polymer Film

Abstract: The biodegradability problem of polymer waste is one of the fatal pollutFions to the environment. Enzymes play an essential role in increasing the biodegradability of polymers. In a previous study, antistatic polymer film based on poly(lactic acid) (PLA) as a matrix and polyaniline (PAni) as a conductive filler, was prepared. To solve the problem of polymer wastes pollution, a crazing technique was applied to the prepared polymer film (PLA/PAni) to enhance the action of enzymes in the biodegradation of polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Mesh implantation within an oxidative stress environment, in this study H 2 O 2 , further promotes an increase in surface crazing through exposure to oxidative degradation processes. The formation of crazes not only acts as a precursor to larger structural surface cracking, which are expected to affect the mesh material's mechanical properties, [ 31 ] but also can act as a pathway for bulk polymer oxidation. Eventually, surface cracking propagates and exposes greater surface areas thereby making more material available for further degradation.…”
Section: Resultsmentioning
confidence: 99%
“…Mesh implantation within an oxidative stress environment, in this study H 2 O 2 , further promotes an increase in surface crazing through exposure to oxidative degradation processes. The formation of crazes not only acts as a precursor to larger structural surface cracking, which are expected to affect the mesh material's mechanical properties, [ 31 ] but also can act as a pathway for bulk polymer oxidation. Eventually, surface cracking propagates and exposes greater surface areas thereby making more material available for further degradation.…”
Section: Resultsmentioning
confidence: 99%
“…PANI is able to improve upon the chemical and mechanical properties of biopolymers so that they can be more feasible for applications in food packaging [ 64 , 65 , 66 ]. At the same time, studies have shown that biopolymer matrices retain their biodegradability behaviour after the incorporation of PANI [ 29 , 67 , 68 , 69 ]. In fact, the addition of PANI improves the biodegradability of low-density polyethylene film (LDPE) via oxo-biodegradation [ 70 ].…”
Section: Applications Of Pani In the Food Industrymentioning
confidence: 99%
“…The purpose of this Special Issue was to collect original contributions, both research papers and reviews, showing recent results and/or positive advances in the behavior of new sustainable biomaterials under applied mechanical stress, in both static and dynamic modes, and evaluating the characteristics of resistance, moduli and/or viscoelasticity in view of potential applications in biotechnology and biomedicine [4], tissue engineering [5], medical devices [6,7], surgical or dental implants [8], agriculture [9], packaging [3,10,11], textiles [1], automotives [12][13][14], green buildings and construction [15], radiation dosimetry [16], and 3D printing [17][18][19].…”
mentioning
confidence: 99%
“…Hernandez et al investigated the effects of microspheres, carbon fibers, or polyethylene glycol added to polyhydroxybutyrate (PHB) resin on the thermal and mechanical properties of the final compounds [21]. A polymer film based on poly(lactic acid) (PLA) as a matrix and polyaniline (PAni) as a conductive filler was prepared by Wong et al [10], to obtain antistatic properties. Polyaniline was chosen due to to its good biocompatibility and conductivity and excellent performance in combination with a PLA matrix.…”
mentioning
confidence: 99%